Estacionalidad y demanda de pasajes aéreos de la agencia de viajes Jungle Tours & Travels E.I.R.L Iquitos período 2020-2024 - Del Aguila Acuy, Maria Fernanda (2025)
The research consists of a basic, quantitative, and descriptive study aimed at analyzing the seasonality (V1) and demand (V2) behavior of airline tickets sold by the travel agency Jungle Tours & Travels E.I.R.L., Iquitos. It presents a non-experimental, longitudinal design, opting to observe the variables in their natural context without intentionally manipulating them, taking data from different time periods, specifically from 2020 to 2024. The study population comprised 60 monthly sales records from the 2020-2024 period. As the sample was equal to the population, the sampling was census-type. General results showed that total revenue from airline ticket sales during the study period reached US$2,296,886.82 (excluding surcharges such as card commissions and ticket remittance), with 2024 leading (37.46%), followed by the years 2021 (20.88%), 2023 (18.44%), 2022 (18.01%), and 2020 (5.21%), indicating a progressive post-pandemic recovery, with 2024 as the year with the highest contribution. The destinations with the highest revenue contributions were Iquitos (25.09%), Lima (20.54%), Cancun-Mexico (19.41%), Dubai (6.73%), and Madrid-Spain (5.74%). The monthly distribution of peak revenues showed August (23.10%) and January (21.06%) as the top months, with other notable months being July (8.60%), December (7.99%), and November (5.62%), and more moderate participations between 4.11% and 5.31% for the remaining months. The total issuance of airline tickets was 4,138, with main destinations in Lima (39.30%), Iquitos (34.25%), Cancun Mexico (4.83%), Cartagena-Colombia (3.05%), and Dubai (2.39%), showing a concentration in domestic destinations.